Chemical composition and screening for antifungal activity of Allamanda spp. (Apocynaceae) crude extracts against Colletotrichum gloeosporioides, causal agent of anthracnose in papaya - Haron, Farah Farhanah; Sijam, Kamaruzaman; Omar, Dzolkhifli; Rahmani, Mawardi (American-Eurasian Network for Scientific Information, 2013)
Leaf extracts of Allamanda blanchetti, Allamanda cathartica, Allamanda cathartica ‘Alba’, Allamanda cathartica ‘Jamaican Sunset’ and Allamanda oenotheraefolia were screened for antifungal activities in vitro and in vivo. The results from all experiments proved that petroleum ether, chloroform and methanol extracts of all plants possessed fungistatic or fungicidal properties on growth of Colletotrichum gloeosporioides which increased at higher extract concentrations. Scanning electron microscope observations showed that active extracts resulted in hyphal degradation where hyphae were retarded. A significantly lower disease incidence, severity, and index were observed in Allamanda treated papaya fruits. Fruits coated with chloroform extracts of A. blanchetti A. cathartica ‘Alba’, and A. cathartica ‘Jamaican Sunset’ showed maximum reduction in anthracnose incidence and severity scores were always 1 (1-25%) and 0 (0%). Antifungal effects of the most effective extracts were supported by the presence of chemical constituents indentified by GC-MS. Campesterol, -sitosterol, stigmasterol, plumericin, squalene, and α-Tocopherol were detected as major compounds in Allamanda species that were possibly responsible for the antifungal activity.